Cultivating Grit in Higher Education: Exploring the Influence of Growth Mindset among University Students (Educational Psychology Journal, 2023)
A good quality of life, one of which is judged by success. This usually starts from taking education. Various challenges and obstacles faced while studying. One of the psychological variables that play a role in dealing with it is academic grit. Individuals who are consistent with their interests and diligently try are predicted to achieve success more easily. Students who are active in organizations are faced with more diverse academic challenges than those who focus solely on academics. Academic grit in student organizations is being questioned. One of the influencing factors is the growth mindset. The subjects of this study were students who were active in organizations. The sampling technique used is cluster random sampling. The research method uses correlational quantitative. Data obtained through the grit scale and growth mindset. The results of the study show that the growth mindset has an influence on the academic grit of students who join organizations. Further research also examines the amount of growth mindset's effective contribution to academic grit as well as some suggestions for future researchers.